Ghana’s progress towards measles elimination: Surveillance data analysis, Greater Accra Region, 2015 – 2019 - Sheriff, Amara Alhaji; Zakariah, Adam; Dapaa, Samuel; Odikro, Magdalene A.; Issahaku, Razak G.; Bandoh, Delia; Noora, Charles L.; Gebru, Gebrekrstos N.; Kenu, Ernest (Frontiers in Tropical Diseases, 2023)
Introduction Although measles is targeted for global elimination by 2020, an estimated 869,770 measles cases and 207,500 deaths occurred in 2019. Ghana adopted the World Health Organization measles elimination strategies, however, evidence of a systematic, comprehensive analysis of data tracking progress towards elimination is sparse. We analyzed measles data to describe its epidemiology, surveillance, and vaccination coverage performances in the Greater Accra Region. Methods We reviewed and conducted a descriptive analysis of measles surveillance, laboratory, and vaccination data for 2015 to 2019 obtained from the regional health directorate and National public health reference laboratory. Case patients’ demographic and clinical variables were analyzed into frequencies, proportions, and rates. We used WHO measles elimination performance targets; at least one suspected measles case reported per 100,000 population, 80% of suspected measles cases investigated with adequate blood samples, measles incidence <1/1,000,000 population, 95% routine vaccination coverage and during SIAs as benchmarks. Results Of 930 suspected measles cases reported, 605(65.1%) were tested. Males accounted for 356(58.8%); 141(23.3%), 342(56.5%), and 122(20.2%), were children <1, 1–4, and ≥5 years old respectively. Of those tested, 10(1.65%) were measles IgM confirmed, of which 7(70.0%) had received at least one dose of measles vaccine. Annualized measles reporting rate ranged from 1.8 to 6.4 per 100,000 population from 2015 to 2019. District specimen collection rate was 100%, and measles incidence was between 0 – 0.6 per million population in the period 2015–2019. Measles vaccination coverage increased from 73.5% in 2016 to 102% in 2019 with 75% of districts achieving 95% coverage in 2019. Conclusion The measles case-based surveillance system and vaccination program in the Greater Accra region showed an increasing level of performance towards Ghana’s elimination status. However, performance in laboratory testing of blood specimens was suboptimal. Authorities of Ghana’s health system should strengthen laboratory capacity for prompt diagnosis of measles.